2000
DOI: 10.1007/s001050050017
|View full text |Cite
|
Sign up to set email alerts
|

Kombination der Antimalariamittel Mepacrin und Chloroquin bei therapieresistentem kutanem Lupus erythematodes

Abstract: Antimalarials represent the first line in treatment of cutaneous lupus erythematosus (LE). However, some patients show no improvement on monotherapy with chloroquine or hydroxychloroquine. A 30-year-old female patient had treatment-resistant cutaneous LE exhibiting features of both LE tumidus and subacute cutaneous LE. Previously, the patient had been unsuccessfully treated with chloroquine, hydroxychloroquine, dapsone, and azathioprine, each in combination with variable doses of prednisolone. However, the LE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…35 Some authors believe that HCQ is safer but less effective than CQ considering the well-known side-effects, such as irreversible retinopathy. [41][42][43] The results of the present study suggest that quinacrine is highly efficient in patients with CLE; however, only a low number of patients applying quinacrine were included in the study. 37 The results of the present analysis demonstrated a slightly higher efficacy of HCQ (86Á9%) compared with CQ (81Á5%) in all CLE subtypes.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…35 Some authors believe that HCQ is safer but less effective than CQ considering the well-known side-effects, such as irreversible retinopathy. [41][42][43] The results of the present study suggest that quinacrine is highly efficient in patients with CLE; however, only a low number of patients applying quinacrine were included in the study. 37 The results of the present analysis demonstrated a slightly higher efficacy of HCQ (86Á9%) compared with CQ (81Á5%) in all CLE subtypes.…”
Section: Discussionmentioning
confidence: 76%
“…39 Moreover, a recently published prospective longitudinal cohort study of 128 patients with CLE, 40 as well as several case reports, confirmed that a combination of HCQ or CQ with quinacrine, respectively, is highly effective. [41][42][43] The results of the present study suggest that quinacrine is highly efficient in patients with CLE; however, only a low number of patients applying quinacrine were included in the study.…”
Section: Discussionmentioning
confidence: 76%
“…Some patients do not respond well to monotherapy with either hydroxychloroquine or chloroquine, and in such cases the addition of mepacrine may be of benefit. 15 In general, hydroxychloroquine and mepacrine are safe, well-tolerated drugs and adverse effects are relatively few, the most widely recognized being retinal toxicity. 16 Chloroquine causes macular pigmentation that progresses to a typical bull's eye lesion and then to widespread retinal pigment epithelial atrophy resembling retinitis pigmentosa.…”
Section: Antimalarialsmentioning
confidence: 99%
“…Several case reports have been published demonstrating that the combination therapy is highly efficient in patients with different subtypes of CLE (DLE, SCLE, and LE panniculitis). [92][93][94] Moreover, quinacrine (100 mg per day) was added in patients with SLE, who were maintained on prednisolone and hydroxychloroquine (some also on azathioprine). 95 Three months after the initiation of quinacrine treatment, disease activity measured by the SLE Disease Activity Index and anti-double-stranded DNA and anticardiolipin antibodies were reduced, followed by reduction or discontinuation of prednisolone in all patients and azathioprine in some patients.…”
Section: Dosage Of Quinacrinementioning
confidence: 99%